A review of mathematical model-based scenario analysis and interventions for COVID-19. (September 2021) - Padmanabhan, Regina; Abed, Hadeel S.; Meskin, Nader; Khattab, Tamer; Shraim, Mujahed; Al-Hitmi, Mohammed Abdulla
Highlights: 12 mathematical models that are used to conduct scenario-based analysis are presented. A general unified model is presented and used to compare 12 models. Model parameters affected by various interventions are highlighted. Active control methods used to combat COVID-19 are reviewed. Abstract: Mathematical model-based analysis has proven its potential as a critical tool in the battle against COVID-19 by enabling better understanding of the disease transmission dynamics, deeper analysis of the cost-effectiveness of various scenarios, and more accurate forecast of the trends with and without interventions. However, due to the outpouring of information and disparity between reported mathematical models, there exists a need for a more concise and unified discussion pertaining to the mathematical modeling of COVID-19 to overcome related skepticism. Towards this goal, this paper presents a review of mathematical model-based scenario analysis and interventions for COVID-19 with the main objectives of (1) including a brief overview of the existing reviews on mathematical models, (2) providing an integrated framework to unify models, (3) investigating various mitigation strategies and model parameters that reflect the effect of interventions, (4) discussing different mathematical models used to conduct scenario-based analysis, and (5) surveying active control methods used to combat COVID-19.